2011
DOI: 10.1111/j.1745-4514.2010.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effects of Pure Black Tea Theaflavins on the Growth of Four Selected Human Cancer Cells

Abstract: The growth inhibition and cytotoxic effects of theaflavins mixture and pure theaflavins [theaflavin, theaflavins-3-gallate, theaflavins-3′-gallate and theaflavin-3, 3′-digallate] from black tea on human liver cancer HepG2 cells, gastric cancer SGC-7901 cells, lung cancer A549 cells and acute promyelocytic leukemia K562 cells were investigated. The four major theaflavins were obtained from enzymatically oxidized catechins mixture using preparative high-performance liquid chromatography (HPLC). The purity and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…It’s orange-red in color and possesses a benzotropolone skeleton that is formed from the co-oxidation of (–)-epicatechin gallate and (–)-epigallocatechin gallate (EGCG) during black tea production (Finger, 1994). TF3 has been demonstrated to inhibit human prostate cancer cells (Lee, Ho, & Lin, 2004; Sun, et al, 2013), liver cancer cells, gastric cancer cells and lung cancer cells (K. Wang, et al, 2011). TF3 exerted antitumor effects in breast cancer cells through suppressing proteasomal activities (Lin, Chen, & Lin-Shiau, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It’s orange-red in color and possesses a benzotropolone skeleton that is formed from the co-oxidation of (–)-epicatechin gallate and (–)-epigallocatechin gallate (EGCG) during black tea production (Finger, 1994). TF3 has been demonstrated to inhibit human prostate cancer cells (Lee, Ho, & Lin, 2004; Sun, et al, 2013), liver cancer cells, gastric cancer cells and lung cancer cells (K. Wang, et al, 2011). TF3 exerted antitumor effects in breast cancer cells through suppressing proteasomal activities (Lin, Chen, & Lin-Shiau, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…TF3 is a polyphenolic compound extracted from black tea and is formed via the co-oxidation of (−)-epigallocatechin gallate (EGCG) and (−)-epicatechin gallate during black tea production [ 17 ]. TF3 has shown potent antioxidant [ 18 ], anti-inflammatory [ 19 ], and anticancer properties [ 20 , 21 , 22 ]. We have previously reported that TF3 inhibited human ovarian cancer cells by inducing apoptosis and cell cycle arrest [ 23 ] and by suppressing angiogenesis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it requires organic acids to assist the separation and avoid the overlapping between theaflavins and catechins. Since the frequently chosen organic acids (Wang et al, ; Xu et al, ) are formic acid, acetic acid, phosphate acid, trifluoroacetic acid that are difficult to get rid of. The concentrated theaflavins fractions are always washed repeatedly with water to remove the residual acid.…”
Section: Resultsmentioning
confidence: 99%